The Effectiveness of Ultrasound-Guided Subacromial-Subdeltoid Bursa Combined With Long Head of the Biceps Tendon Sheath Corticosteroid Injection for Hemiplegic Shoulder Pain: A Randomized Controlled Trial - Hou, Yajing; Zhang, Tong; Liu, Wei; Lu, Minjie; Wang, Yong (Frontiers in Neurology, 2022)
Background: Subacromial-subdeltoid (SASD) bursa and long head of the biceps tendon (LHBT) sheath corticosteroid injection are commonly used to treat shoulder pain associated with arthritic shoulder conditions, but effectiveness in the stroke population is unclear. This study aimed to investigate the clinical effectiveness of ultrasound-guided SASD bursa combined with LHBT sheath corticosteroid injection for hemiplegic shoulder pain (HSP) compared with SASD bursa injection alone. Methods: 60 Patients with HSP were randomly allocated to the dual-target group (n=30) and single-target group (n=30). The single-target group received SASD bursa corticosteroid injection alone, and the dual-target group received SASD bursa and LHBT sheath corticosteroid injection. The primary endpoint was pain intensity measured on a visual analog scale (VAS). The secondary endpoint was passive range of motion (PROM) of the shoulder, Upper Extremity Fugl-Meyer assessment (UEFMA) score, and Modified Barthel Index (MBI) score. PROM and pain intensity VAS were assessed at baseline and weeks 1, 4 and 12 post-treatment. UEFMA and MBI were recorded at baseline and weeks 4 and 12 post-treatment. Results: A total of 141 patients with HSP were screened, and 60 patients were included. Significant differences in the VAS, PROM, UEFMA and MBI were observed at all follow-ups in both groups. The dual-target group showed a significant difference in VAS score compared with the single-target group (3.3 vs. 3.7, P=.01) at week 4 and week 12 (2.5 vs. 3.2, P<.001). Moreover, the dual-target group showed statistically significant differences in flexion (P<.001) at week 12, extension rotation (P<.001) at week 12, and abduction at week 1 (P=.003) and weeks 4 and 12 (P<.001) compared with the single-target group. There were significant differences in FMA and MBI scores in the two groups before and after treatment (P<.001), with a more significant increase in the dual-target group compared with the single-target group (P<.001) at week 12. Conclusion: The combination of SASD bursa and LHBT sheath corticosteroid injection is superior to SASD bursa injection alone in reducing shoulder pain and improving functional activities in patients with HSP. Keywords: hemiplegic shoulder pain, subacromial-subdeltoid bursa corticosteroid injection, biceps tendon sheath corticosteroid injection, combined therapy, ultrasound-guided